Effect of different cleansing agents and adhesive resins on bond strength of contaminated zirconia. Issue 3 (July 2019) - Wattanasirmkit, Kamolporn; Charasseangpaisarn, Taksid
Abstract: Purpose: This study was observed the effect of cleansing agents and adhesive resins on shear bond strength (SBS), surface morphology and phase transformation of saliva and silicone disclosing medium contaminated zirconia. Methods: The 110 zirconia specimens size 5 × 5 × 1 mm were fabricated and randomly divided into 5 surface treated groups: Non-contaminated (PC) Saliva and silicone disclosing medium contaminated without cleansing (NC) Surface contaminated and cleansing with Phosphoric acid (PO) Ivoclean (IC) or Hydrofluoric acid (HF). The twenty of each surface treated specimens were selected and bonded with Panavia F2.0 (P) and Superbond C&B (S) for SBS test (n = 10). The data was analyzed by Kruskal–Wallis H and Mann–Whitney U test. The remaining specimens of each surface treated groups were examined by SEM and XRD. Results: The saliva and silicone disclosing medium contaminated zirconia without cleansing group (PNC) had the lowest SBS when Panavia F2.0 was used for cementation (p < 0.05). The SBS of surface cleansing groups (PPO, PIC and PHF) were not different from the non-contaminated group (PPC) (p > 0.05). However, there were no difference in SBS among groups when cementation with Superbond C&B (SPC, SNC, SPO, SIC and SHF) (p > 0.05). There was no morphologic changing that could be observed by SEM. The XRD showed little phase transformation when surfaces were contaminated and cleaned. Conclusions: The saliva and silicone disclosing medium contaminated zirconia should be cleaned with Phosphoric acid, Ivoclean or Hydrofluoric acid for 20 s prior to cementation with Panavia F2.0. However, the surface cleansing was not necessary when cementation with Superbond C&B.